Development of Integrated Thematic Learning Model based on Islamic Values in Madrasah Ibtidaiyah of Padang City - Sasmi Nelwati; Marsidin Marsidin; Nizwardi Jalinus; Mukhaiyar Mukhaiyar (Universitas Negeri Padang, 2018)
The purpose of this research is to develop an integrated thematic learning model based on Islamic values in Madrasah Ibtidaiyah practically and effectively. The type of this research is development research that refers to the model of 4D. The distribution of this model is implemented in Madrasah Ibtidaiyah of Padang city in 2016. The types of data are qualitative and quantitative data. Qualitative data are derived from observation and interview. Furthermore, quantitative data are obtained from questionnaire. The products of integrated thematic learning model based on Islamic values which have been developed are model guidebook, educator guidebook, and student guidebook. The achievement of the research results indicate that the three products have meet the criteria of validality, practicality and effectiveness. The book model can be used by educators/ teachers and students of elementry school level in helping the students become active and having a good character.